Delovanje Gregorja Kocijana na Pedagoški fakulteti v Ljubljani - Blažič, Milena (Jezik in slovstvo, 2013)
The central part of the bio-bibliography of Gregor Kocijan is represented by his lectureship at his affiliate institution - the Pedagogical Academy, later the Ljubljana Faculty of Education (from 1975 until his retirement on 31 December 1998), where he taught General (and Youth) Literature, while Youth Literature was taught by Marjana Kobe. In the Bologna reform, the subject was divided into two parts: Introduction to Literature, and Youth Literature. Due to the restructuring of the Ljubljana Pedagogical Academy, which once educated teachers of Slovene at all of the levels of eight-year primary school,but later only teachers at class-level primary school, Kocijan was asked to also teach at the Koper unit of the Faculty of Education and the Maribor Faculty of Education, as well as at the Ljubljana Faculty of Arts. His main scientific research interest was Slovene short narrative prose, which he treated in the reading materials for the higher grades of primary school, i.e., from the fifth to the ninth grade of primary school.
Keywords: Kocijan, Gregor, 1933-; Slovene literature; slovenska književnost; berila; kratka proza; literarni zgodovinarji; literary historian; biografije; bibliografije